Пошаговое объяснение:
-12 + (-13) = -12 - 13 = -25
0 + (-6) = 0 - 6 = -6
47 + (+131) = 47 + 131 = 178
-16 + (-14) = -16 - 14 = -30
а)-12+(-13)= -(12+13)= -25
б)0+(-6)=0-6= -6
в)47+(+131)=47+131=178
г)-16+(-14)= -(16+14)= -30
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
-12 + (-13) = -12 - 13 = -25
0 + (-6) = 0 - 6 = -6
47 + (+131) = 47 + 131 = 178
-16 + (-14) = -16 - 14 = -30
Verified answer
а)-12+(-13)= -(12+13)= -25
б)0+(-6)=0-6= -6
в)47+(+131)=47+131=178
г)-16+(-14)= -(16+14)= -30